Effect of Leverage, Liquidity, Intensity of Fixed Assets, and Company Size on Tax Aggressiveness: Pengaruh Leverage, Likuiditas, Intensitas Aset Tetap, dan Ukuran Perusahaan Terhadap Agresivitas Pajak - Nurindah Rizkyah Safitri; Imelda Dian Rahmawati (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze the Effect of Leverage, Liquidity, Fixed Asset Intensity, and Firm Size on Tax Aggressiveness (Study on Consumer Goods Industrial Sector Companies Listed on the Indonesia Stock Exchange 2016-2019 Period). The sampling method used is purposive sampling method. The number of companies that were sampled in this study were 26 companies in the Consumer Goods Industry Sector listed on the IDX in the 2016-2019 period. The data used is secondary data. The data analysis method used in this study is Multiple Linear Regression with the help of the SPSS 23 analysis tool. The results of this study indicate that Leverage Affects Tax Aggressiveness in Consumer Goods Industry sector companies for the 2016-2019 period. Liquidity Affects Tax Aggressiveness in Companies in the Consumer Goods Industry sector for the 2016-2019 period. Intensity of Fixed Assets Affects Tax Aggressiveness in Consumer Goods Industry sector companies for the 2016-2019 period. Company Size Affects Tax Aggressiveness in Consumer Goods Industry Sector Companies Listed on the Indonesia Stock Exchange for the 2016-2019 Period